Systematic Review of Literature on Single-Nucleotide Polymorphisms Within the Oxytocin and Vasopressin Receptor Genes in the Development of Social Cognition Dysfunctions in Individuals Suffering From Autism Spectrum Disorder - Wilczyński, Krzysztof Maria; Siwiec, Andrzej; Janas-Kozik, Małgorzata (Frontiers in Psychiatry, 2019)
Introduction: The autism spectrum disorder (ASD) is a nosological unit present in virtually all populations regardless of their ethnic or socioeconomic backgrounds. Symptoms dominating the picture of autism persistent throughout the course of development include, inter allia, qualitative disorders of social communication and social interactions. Numerous studies on animal models as well as groups of healthy individuals assessing the potential role of oxytocynergic and vasopresynergic systems in normal social functioning have also discussed their potential participation in the development of social cognition dysfunctions in the course of ASD. The purpose of this study was to conduct a systematic review of literature regarding the role of polymorphisms within genes for oxytocin and vasopressin receptors in the development of social cognition dysfunctions in individuals suffering from ASD. Methods: A systematic review of literature published within the last 10 years and accessible in PubMed, Google Scholar, Cochrane Library and APA PsycNET databases, was conducted by each author separately. Inclusion criteria required that articles be (1) published between January 2008 and August 2018; (2) published in the English or Polish language; (3) located in periodical publications; (4) focused on the role of polymorphisms within oxytocin and vasopressin receptor genes in autistic population; (5) provided a clear presentation of utilized methodology; (6) utilized proper methodology. Results: Out of the 491 studies qualified to the initial abstract analysis, 19 were included into the full-text review based on the above six inclusion criteria. Conclusions: The analysis of available literature seems to indicate that there is an association between social cognition dysfunctions in the course of autism and selected alleles of polymorphisms within the OXTR and AVPr1a genes. However, previous studies do not allow to specify the nature of this association in an unequivocal way nor to select genotypes which are the basis for this association.